Estudo das propriedades de filmes finos de ITO/Cu2O produzidos por eletrodeposição - (:unkn) unknown (Universidade Federal do Pampa, 2022)
With the growing global demand for electrical energy, traditional sources are not being enough anymore and an option with great potential to supply this demand is the solar radiation, which makes it possible to obtain pollutant free electrical energy. Alternatives search for converting sunlight into electricity, using the photovoltaic effects, is of interest to many researches. Photovoltaic cells are made of semiconductors and, increasingly, alternative materials are being sought, like in the area of thin films. A compound explored in many applications and that attracted the attention of the scientific community is cuprous oxide (Cu2O), due to its optical and electrical characteristics, high abundance in nature, low toxicity and low cost; besides being a p type semiconductor material, which in some situations can be transformed into n-type semiconductor. All this contributed to a high importance of Cu2O in the use of solar cells. Because of this, the objective of this work is to obtain, through electrodeposition, thin semiconductor films of Cu2O on ITO/glass substrate for possible applications in solar cells. Cyclic voltammetry was performed, in order to obtain the chemical reactions that occur in the substrate and locate electrical potentials. And also the electrodeposition technique, from that, it is possible to estimate the thickness of cuprous oxide produced on the ITO, through the current transients were made that indicate about the growth of the material. For both techniques, an electrochemical cell with three electrodes connected to a potentiostat was used. The characterization of the structural properties, such as crystal orientation and crystallite size, was carried out through X-ray diffractometry. The investigation of the surface morphology, such as roughness and grain size, was carried out by atomic force microscopy. Finally, the identification of the behavior of the semiconductor films produced and the evaluation of their stability through photoelectrochemical measurements. The results achieved were satisfactory and important, obtaining economically viable thin films of good quality.
Keywords: Células solares; Eletrodeposição; Filmes finos; ITO; Óxido cuproso; Solar cells; Electrodeposition; Thin films; Cuprous oxide; CNPQ::ENGENHARIAS